LAS VISITAS PASTORALES COMO FUENTE PARA EL ESTUDIO DE LA HISTORIA DE LA METEOROLOGÍA EN COSTA RICA (1850-1921) - Díaz Bolaños, Ronald Eduardo (2008)
The chronicles of the pastoral visits have long been a source of data for history research since they describe the social, economic, political, and cultural aspects of the different localities visited by the ordinary bishops of the dioceses. Moreover, these records also provide information on aspects related with the state of climate and weather of the places visited. In the particular case of Costa Rica, the record of the pastoral visits kept at the Archdiocesan History Archives Mons. Bernardo Augusto Thiel Hoffmann provide valuable data pertaining to the qualitative aspects of weather and climate of the many localities and regions that lacked meteorological records through specialized instruments. Therefore, this data compilation has proven useful in the reconstruction of the perceptions and representations of weather and climate in the sites visited by the bishops of the Diocese of San José, Costa Rica during the period 1850-1921.